Interpersonal Spirituality between College Students and Fathers - Brelsford, Gina M. (Research in the social scientific study of religion, 2010)
This study examined the link between interpersonal spirituality, specifically spiritual disclosure, and father-child relationship quality for 76 fathers and 454 college students. spiritual disclosure is defined as a discussion of religious and spiritual beliefs and practices between fathers and their college-aged children. results from this study found that fathers and college students who reported higher levels of spiritual disclosure also indicated greater relationship satisfaction, higher levels of open family communication, and greater intrapersonal religiousness and spirituality. Further, father and college students’ reports on spiritual disclosure predicted unique variance to father-child relationship quality after accounting for demographics, intrapersonal religious dimensions, and relationship quality indicators. These findings support the saliency of spiritual disclosure for father-child relationships and intrapersonal religious and spiritual development.